On Some Characterizations of Vector Fields on Manifolds - Ahmed, Khondokar M.; Raknuzzaman, Md.; Ali, Md. Showkat (Dhaka University Journal of Science, 2012)
The basic geometry of vector fields and definition of the notions of tangent bundles are developed in an essential different way than in usual differential geometry. ø-related vector fields are studied and some related properties are developed in our paper. Finally, a theorem 5.04 on our natural injection j of submanifolds which is j-related to vector field X is treated. DOI: http://dx.doi.org/10.3329/dujs.v60i2.11530 Dhaka Univ. J. Sci. 60(2): 259-263, 2012 (July)